A new species of Tyrodes Raffray (Coleoptera: Staphylinidae: Pselaphinae) from China - Zhang, Yong-Qin; Yin, Zi-Wei (Zootaxa, 2023)
A new species of the small pselaphine genus Tyrodes Raffray (Pselaphitae: Tyrini), T. tibialis sp. nov., is described and illustrated from Guangxi, southwestern China. This species can be separated from its congeners mainly by the aedeagal characters as well as by the modified sternite 2 (V), and presence of a preapical projection of the metatibiae.